The ranking of factors in selecting the online shopping platform in Malaysia based on fuzzy analytic hierarchy process / Khairu Azlan Abd Aziz ... [et al.] - Abd Aziz, Khairu Azlan; Wan Daud, Wan Suhana; Mohd Idris, Mohd Fazril Izhar; Zakaria, Siti Nurmaisarah (UiTM Cawangan Perlis, 2024)
There is an increasing number of online shopping platforms nowadays. People sometimes may have difficulties in choosing an ideal online shopping platform to suit their wants and needs. This study aims to rank the factors that influence consumers in selecting an online shopping platform in Malaysia. The Fuzzy Analytic Hierarchy Process is employed in this study to accomplish its objectives by ranking four factors: user-friendliness, trustworthiness, price and promotion, and responsiveness. The decision-makers for this study include an executive marketer from a business company and a lecturer with marketing expertise from UiTM Arau, Perlis. The results highlight a clear trend, indicating that pricing and promotions are the most important factors, holding the highest normalized weight. Subsequent in significance are user-friendliness, trustworthiness, and responsiveness. This insight into the hierarchical significance of these factors contributes valuable perspectives for both academics and practitioner in the field of online shopping platforms.